Communication Students Perception Of The Impact Of TikTok Use In Forming Cultural Identity And Nationalism In The Era Of Globalization - Putri, Yori Maharani; Afriliyan, Rahmatul; Ramadhan, Syahrul; Setyawan, Zidan; Sari, Diaz (Universitas Dharmawangsa Medan, 2025)
This study examines the perceptions of students in the Communication Science Program at Universitas Muhammadiyah Riau on the impact of TikTok usage in shaping cultural identity and nationalism in the era of globalization. The research aims to analyze how TikTok, as a popular digital social media platform, influences students’ views and attitudes toward local culture and national identity. Using a mixed-method approach through questionnaires distributed to 50 respondents and in-depth interviews with active TikTok users, this study explores patterns of content consumption and production related to cultural and national themes. The findings indicate that while TikTok enables students to express and promote local cultural elements—such as traditional dances, local cuisine, and regional languages—there is also a risk of cultural identity dilution due to exposure to global content. Regarding nationalism, the results show limited active engagement, as students tend to consume rather than produce content with nationalistic messages. The study highlights the relevance of Uses and Gratifications Theory, Social Identity Theory, and Digital Nationalism Theory in understanding these phenomena. In conclusion, TikTok has the potential to strengthen cultural identity and nationalism among youth if used wisely and creatively. Educational institutions and policymakers are encouraged to facilitate programs and digital literacy to support the creation of cultural and national content that appeals to young audiences.